Produtividade e persistência de forrageiras exóticas adaptadas ao semiárido manejadas sob alturas residuais - Torres, Antônia Flávia Fernandes (2021)
The objective of this study was to evaluate the effects of different residual heights on the productivity and persistence of adapted exotic forages (buffel grass: Pennisetum ciliare cv. Molopo; urochloa grass: Urochloa mosambicensis and massai grass: Megathyrsus maximus cv. Massai) cultivated in the Semiarid Brazilian. The experiment was conducted at the Teaching, Research and Extension Unit (UEPE) of the Federal Institute of Education, Science and Technology of Ceará (IFCE), in Chapada do Apodi, in Limoeiro do Norte/CE. A randomized block design was used, with different residual heights (RH) in an arrangement of subdivided plots, with the seasons being the plots (dry and rainy season) and the residual heights being the subplots (5; 10; 15 and 20 cm in relation to the ground), with 4 repetitions in each. During the establishment season, there was an effect of the evaluation cycles on the variables evaluated, observing that despite a decrease in total forage biomass (TFB) of the buffel grass, there was a condition of persistence of the canopy to successive cuts, determined by the maintenance of plant height (PH) and tiller population density (TPD), while massai grass and urochloa grass showed a reduction of these variables during the evaluation cycles. There was an effect of RH and periods of evaluation on all variables evaluated during the dry season, with an increasing linear response on the residual forage biomass (RFB) with the increase in RH of the grasses evaluated. With respect to massai grass and urochloa grass, no difference was observed in litter biomass (LB) during the dry season. It was found that as the RH increased, there was an increase in RFB, with a lower harvestable forage biomass (HFB) for all grasses evaluated during the rainy season. The TFB of buffel grass showed a quadratic response, with a minimum value of 8,264.7 kg ha-1 in the 12.8 cm RH. A quadratic response was observed for the TPD of massai grass during the 1st evaluation period, with a maximum value of 634 tillers m-2, in the RH of 11.6 cm. Pearson’s correlation analysis indicated a strong positive correlation for all grasses evaluated for CANOPYHEIGHTxNDVI, with R²=0.66; 0.90 and 0.81 for buffel grass, massai grass and urochloa grass, respectively. Buffel grass pastures managed under lower RH present adaptive characteristics, with high productivity and high tiller production, without compromising the pasture's longevity, while pastures formed by massai grass and urochloa grass demonstrate that a higher residual height would be ideal for provide full vigor of regrowth and development.